The labor market in India since the 1990s - Indraneel Dasgupta; Saibal Kar (IZA World of Labor, 2018)
The Indian economy entered an ongoing process of trade liberalization, domestic deregulation, and privatization of public sector units in 1991. Since then, per capita output has increased significantly, while the overall unemployment rate has remained low. However, labor force participation rates have fallen sharply, especially for women. In addition, youth unemployment remains stubbornly high, an overwhelming proportion of the labor force continues to work in the informal sector, and there is little evidence of a sustained rise in wages for either unskilled rural or factory workers.
Keywords: L16; O40; J46; J21; 330; wage rate; unemployment; labor force participation rate; India